Comparing the Movement System Impairment Method and Routine Physical Therapy for Knee Pain: A Randomized Clinical Trial - Mohammadreza Farazdaghi; Hassan Sadeghi; Marjan Alipour Haghighi; Salem M. Alshammari (Life)
This study explores the effectiveness of the Movement System Impairment (MSI) model compared to traditional physiotherapy for treating knee pain. Fifty patients with unilateral knee pain participated, with their femur, tibia, and knee alignment assessed in nine functional positions. Evaluations included the Tegner Activity Scale, Knee Injury and Osteoarthritis Outcome Score (KOOS), muscle power, extensibility, and pain levels. Patients were randomly assigned to either the MSI treatment group, which focused on identifying and correcting faulty movements, or a routine physiotherapy group that received general strengthening and stretching exercises. Results indicated that both treatment approaches improved muscle power in hip abductors and lateral rotators, as well as scores on the Tegner Activity Scale and the KOOS. Notably, the MSI group demonstrated greater improvements in the muscle power of the hip lateral rotators and knee extensors and a significant reduction in knee pain during walking compared to the routine group (p = 0.005). In conclusion, both treatments enhanced pain, function, and muscle strength, while the MSI model significantly reduced knee pain in walking and improved hip and knee muscle power compared to routine physiotherapy.